1984
DOI: 10.1007/bf01419377
|View full text |Cite
|
Sign up to set email alerts
|

On the structure of two-quasiparticle states in even-A Xe isotopes

Abstract: The excitation energies of proton and neutron two-quasiparticle states in even-A xenon isotopes are studied within the shell-model framework. The results suggest that in the lighter isotopes (A__< 126) the proton excitations might be yrast, whereas in the heavier ones (A>130) the neutron-hole excitations dominate at lower energies. This finding would then explain the complex excitation spectra found in 126'128'13~ where the two excitation modes occur at comparable energies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

1984
1984
2006
2006

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
1
1
1
Order By: Relevance
“…This value is in good agreement with the experimentally determined energy (E exp = 2.23 MeV) and with previous work [22], where an equivalent ν(1h −1 11/2 3s −1 1/2 ) two-hole configuration with a calculated energy of ∼2.4 MeV was proposed for this state. The middle panel of Fig.…”
Section: -7supporting
confidence: 92%
“…This value is in good agreement with the experimentally determined energy (E exp = 2.23 MeV) and with previous work [22], where an equivalent ν(1h −1 11/2 3s −1 1/2 ) two-hole configuration with a calculated energy of ∼2.4 MeV was proposed for this state. The middle panel of Fig.…”
Section: -7supporting
confidence: 92%
“…A v 28---+~27-transition could be very much retarded. This, on the other hand, is in disagreement with the results of a recent calculation of two-quasiparticle energies in even Xe isotopes [28]. Finally, we comment on the possibility of the v(gv/2g9/2)8+ configuration for the isomer in 12SXe.…”
Section: Isomeric Half-livescontrasting
confidence: 61%
“…The nature of the above-mentioned two-quasiparticle states is unknown because the neutron and proton two-quasiparticle states in this region of nuclei occur at comparable energies. L6nnroth [26] applying the simple shell model approach to the lZSXe nucleus has shown that low-lying two-quasiparticle states belong to the neutron configurations resulting from the coupling of the h~i/2 neutron to the sl/2, d3/2, d5/2, g7/2 or h11/2 neutrons and that proton states lie at higher energies. Recent measurements of the magnetic moment in lZSXe [27] suggest a pure neutron configuration v(h[~ 2 g7-/~)8-for the 8-isomeric state.…”
Section: A New Isomeric State In 127xementioning
confidence: 99%